Chasing chariots : proceedings of the first International Chariot Conference (Cairo 2012) - Ikram, Salima.; Veldmeijer, A. J. (Sidestone Press, 2013)
The present work is the result of the First International Chariot Conference, jointly organised by the Netherlands-Flemish Institute in Cairo (NVIC) and the American University in Cairo (AUC) (30 November to 2 December 2012). The intention of the conference was to make a broad assessment of the current state of knowledge about chariots in Egypt and the Near East, and to provide a forum for discussion. A wide variety of papers are included, ranging from overviews to more detailed studies focusing on a specific topic. These include philology, iconography, archaeology, engineering, history, and conservation. The book is of interest to scholars as well as anyone with an interest in ancient technology, transportation, or warfare.